A Bifunctional "Off‐On" Fluorescence Probe Based on Naphthalene for the Detection of Ag+ and Al3+ and Its Application in Practical Water Samples, as a Logic gate and as Test Paper. Issue 33 (6th September 2021) - Yang, Dong; Zhu, Bin; Zhang, Dongmei; Zhang, Xia; Liu, Wenbo; Xue, Jing; Wei, Yaoyi; Bi, Caifeng; Fan, Yuhua
Abstract: A bifunctional fluorescence probe (PCT) based on 2‐Hydroxy‐1‐naphthaldehyde and thiosemicarbazide was developed. The probe PCT can selectively detect Ag + and Al 3+ with two clear fluorescence color changes from colorless to yellow and blue violet, respectively. According to the Job's plots and mass spectrum, the binding stoichiometry of the probe PCT with Ag + and Al 3+ was 1 : 1, respectively. Moreover, the detection limit values of PCT for Ag + and Al 3+ in neutral solutions were 1.97 and 1.63 nM and these values were remarkably lower than allowed Ag + and Al 3+ concentrations in potable water determined by the World Health Organization (WHO). The distinct different binding mode were elucidated in this paper. Finally, the probe PCT has been used successfully for the detection of Ag + and Al 3+ in real water samples, logic gate and test paper. Abstract : The probe PCT can selectively detect Ag + and Al 3+ with two clear fluorescence color changes from colorless to yellow and blue violet, respectively. The distinct different binding mode were elucidated in this paper. Finally, the probe PCT has been used successfully for the detection of Ag + and Al 3+ in real water samples, logic gate and test paper.